Social Media Policies in University Libraries - Akbaş, Murat; Fenerci, Tülay (Information World, 2016)
Socialmedia, the phenomenon of our era, has been usedby people and organizations widely and profoundly all over the world. This new communication and sharing platform offers many opportunities to its users. However, it has some threats. Therefore, operating, managing and controlling of social media accounts become important and creating a social media policy arises as a necessity. In this article, it has been determined whether the university libraries using social media have a social media policy and it has been tried todetermine the awareness level of the librarians with respect to whether they think that social media policy is a need. A survey has been conducted upon 90 university libraries that use social media and the responses of 67 (74,4 %) participants have been evaluated. The results show that only 7,4 % of the participant have a social media policy created for their library, and the librarians mostly (82%) believe that a document like social media policy should be used by the libraries. With regard to this, a social media policy, which is thought to be a guiding instrument for Turkish university libraries is proposed and presented in this study.